Resource Sharing. SPEC Kit 42 - Association of Research Libraries, Washington, DC. Office of Management Studies; Association of Research Libraries, Washington, DC. Office of Management Studies ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1978)
A 1977 Association of Research Libraries (ARL) survey indicated that nearly all respondents viewed enhanced access to needed information and service capabilities as the primary benefit of resource sharing. Most responding libraries participated in more than one type of resource sharing activity, ranging from informal understandings among a few similar libraries, to formal multi-faceted cooperatives, consortia, or networks that operate over a large region or nationally. The introduction provides a concise summary of current issues and trends related to resource sharing. The collection of documents comprises: resource sharing policies from University of California and University of Connecticut, and the Constitution of the Middle Atlantic Research Libraries Information Network, from Princeton University; resource sharing procedures from University of Houston and Queens University, and the user guide for the Boston Library Consortium from University of Massachusetts; program descriptions/activities from Yale University, McMaster University, University of California/Berkeley, and University of California Berkeley/Stanford Research Cooperative Program; planning and evaluation methods from Yale University and University of Houston; reports and recommmendations from the New York Public Library and Case Western Reserve University (on the Cleveland Area Interlibrary Network and the Cleveland Area Metropolitan Library System); and a 38-item bibliography. (THC)
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Libraries; Consortia; Higher Education; Interlibrary Loans; Library Acquisition; Library Cooperation; Library Materials; Library Networks; Library Planning; Methods; Position Papers; Research Libraries; Shared Services; Collected Works, General; Reports, Descriptive